Cerebrovascular autoregulation in pediatric moyamoya disease. Issue 6 (18th March 2013) - Lee, Jennifer K.; Williams, Monica; Jennings, Jacky M.; Jamrogowicz, Jessica L.; Larson, Abby C.; Jordan, Lori C.; Heitmiller, Eugenie S.; Hogue, Charles W.; Ahn, Edward S.; Davidson, Andrew
Summary Background Moyamoya syndrome carries a high risk of cerebral ischemia, and impaired cerebrovascular autoregulation may play a critical role. Autoregulation indices derived from near‐infrared spectroscopy (NIRS) may clarify hemodynamic goals that conform to the limits of autoregulation. Objectives The aims of this pilot study were to determine whether the NIRS‐derived indices could identify blood pressure ranges that optimize autoregulation and whether autoregulatory function differs between anatomic sides in patients with unilateral vasculopathy. Methods Pediatric patients undergoing indirect surgical revascularization for moyamoya were enrolled sequentially. NIRS‐derived autoregulation indices, the cerebral oximetry index (COx) and the hemoglobin volume index (HVx), were calculated intraoperatively and postoperatively to measure autoregulatory function. The 5‐mmHg ranges of optimal mean arterial blood pressure (MAPOPT) with best autoregulation and the lower limit of autoregulation (LLA) were identified. Results Of seven enrolled patients (aged 2–16 years), six had intraoperative and postoperative autoregulation monitoring and one had only intraoperative monitoring. Intraoperative MAPOPT was identified in six (86%) of seven patients with median values of 60–80 mmHg. Intraoperative LLA was identified in three (43%) patients with median values of 55–65 mmHg. Postoperative MAPOPT was identified in six (100%) of six patients with median values of 70–90 mmHg. Patients with unilateral disease had higher intraoperative HVx (P = 0.012) on side vasculopathy. Conclusions NIRS‐derived indices may identify hemodynamic goals that optimize autoregulation in pediatric moyamoya.